Voces y escuchas situadas del encaje de bolillos en Almagro. - Almansa Ballesteros, Alonso (Re-visiones, 2024)
The text is presented as a space for the mixing of different voices of women lacemarkers. Through situated listening and relying on the bodily itineraries, in the text we hear -we read- the voices of Elena González and Natividad González -among others-. They are voices from Almagro, a own that stands out for its history in the production of bobbin lace. In the text we wander through the tensions, problems and characteristics of bobbin lace and its potentialities as a craft, unproductive from the point of view of the Capitolecene. Far from romanticizing stories or biographies, this work aims to break away from the paradigm of bobbin lace productions -dominated by the invisibility of the lace makers and their needs- thus advocating for the visibility and voice of the lace-making women.
Keywords: bobbin lace; women lacemarkers; bodily itineraries; textile craft; Almagro